The Impact of English Teachers' Feedback Style on Students' Speaking Confidence at Smp Mutiara Terpadu Palabuhanratu - Lela Agustina; Handi Pabriana; Anisa Alawiyyah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Speaking confidence remains a persistent challenge in EFL classrooms, as many students remain reluctant to communicate orally despite the growing demand for English communication skills in the twenty-first century. Students' fear of making mistakes and receiving negative evaluation often limits their participation in speaking activities, underscoring the need to examine the role of teacher feedback in shaping learners' confidence. This study aimed to investigate the characteristics of teacher feedback styles and to explore students' perceptions of how feedback influences their speaking confidence. A qualitative comparative case study design was employed, involving two English teachers and students from Grade VII and Grade VIII at a junior high school. Data were collected through classroom observation and semi-structured interviews and analyzed using Braun and Clarke's (2006) thematic analysis. The findings revealed four major feedback types: corrective, epistemic, suggestive, and combined feedback. Corrective feedback was the most frequently used type overall, whereas supportive feedback practices were more evident in Grade VIII classrooms. Five themes describing students' speaking confidence also emerged: Anxiety-Driven Silence, Authoritative Feedback as Confidence Suppressant, Supportive Feedback as Confidence Catalyst, Recast and Epistemic Feedback as Preferred Intervention, and Teacher as Architect of Speaking Confidence. Students who received supportive feedback demonstrated greater willingness to communicate, more active participation, and higher confidence in speaking English. These findings imply that effective feedback should balance linguistic accuracy with emotional support to foster both speaking development and confidence. The study was limited to a single school context involving two teachers, which constrains the transferability of the findings to other educational settings.